Differences in PpAAT1 Activity in High- and Low-Aroma Peach Varieties Affect γ-Decalactone Production. Issue 4 (30th January 2020) - Peng, Bin; Yu, Mingliang; Zhang, Binbin; Xu, Jianlan; Ma, Ruijuan
Abstract : Sequence differences among ALCOHOL ACYLTRANSFERASES1s likely account for differences in the levels of the aroma compound γ-decalactone between high- and low-aroma peach cultivars. Abstract: Aroma contributes to the unique flavors of fruits and is important for fruit quality evaluation. Among the many volatiles in peach ( Prunus persica ) fruits, γ-decalactone has the greatest contribution to the characteristic peach aroma. Some peach cultivars have γ-decalactone contents that are too low to detect. Comparison of the transcriptomes and metabolomes of a high-aroma cultivar, Fenghuayulu, and a low-aroma cultivar, Achutao, suggested that amino acid substitutions in ALCOHOL ACYLTRANSFERASE (PpAAT1) are responsible for the undetectable levels of γ-decalactone in cv Achutao fruit. Modeling and molecular docking analysis of PpAAT1 indicated that the substituted residues might determine substrate recognition or act as control channels to the active site. In vitro enzyme assays on PpAAT1 heterologously expressed and purified from Escherichia coli and in vivo assays using transient PpAAT1 expression in Nicotiana benthamiana or the oleaginous yeast Yarrowia lipolytica indicated that PpAAT1 from high-aroma cultivars was more efficient than PpAAT1 from low-aroma cultivars in catalyzing the conversion of 4-hydroxydecanoyl-coenzyme A into γ-decalactone. Examination of loss-of-function mutations of PpAAT1 generated by CRISPR/Cas9 in cv Fenghuayulu showed that fruits with PpAAT1 mutations had significantly lower γ-decalactone contents. Expression of the version of PpAAT1 from cv Fenghuayulu in cv Achutao restored γ-decalactone levels to those measured in 'Fenghuayulu', confirming the specific contribution of PpAAT1 to the formation of this key aroma compound. These results show how the biosynthesis of the peach aroma compound γ-decalactone is compromised in some low-aroma cultivars and illustrate the physiological role of PpAAT1 in plant lactone biosynthesis.